Aplikasi Jurnal Kelas Berbasis Web MTs Al Azhar Legari - Muhammad Rofiq; Ester Ayuk Pusvita (STMIK Pesat Nabire, 2024)
In the future, web-based classroom journal applications can continue to evolve with the integration of new technologies such as artificial intelligence for predictive analytics and personalized learning recommendations. Smarter use of data will help improve the student learning experience and the overall efficiency of school management. Thus, the web-based classroom journal application is not just an ordinary administrative tool, but an innovation that supports the transformation of education. This study explores the development and implementation of a web-based classroom monitoring system designed to enhance educational oversight and improve student engagement. The system allows educators to track student attendance, participation, and performance in real-time, facilitating timely interventions for at-risk students. Data were collected through surveys and usage analytics from both educators and students to evaluate the system's effectiveness. Results indicate a significant increase in both teacher satisfaction and student engagement compared to traditional monitoring methods. The findings suggest that web-based monitoring systems can be a valuable tool for modern educational environments, promoting a more interactive and responsive learning experience. Recommendations for further research include exploring the integration of artificial intelligence to personalize student monitoring.